Symbolic Mythology: The Portrayal of Gender Fluidity in Kae Tempest Selected Poems - Okasunu, I Gusti Ayu Sundari; Darma Putra, Darma Putra (Humanis, 2023)
Myth in literary works tends to be used as a traditional story which typically aims to represent and explain certain natural phenomenon. One of those phenomenon are the existence of multi-binary or even non-binary gender which at first known as mythological story of Tiresias that become a real social issue recently. Related to myth, this article is aimed to identify and elaborate the term neutral and gender fluidity correlates to the mythology of Tiresias from Oedipus in the account of hybrid sign by Pierce. Tiresias representing the fluidity term of gender which in the written poems by Tempest’s selected works has symbolical meaning. The data was taken from selected poems in Kae Tempest anthological poetry and collected using proposed sampling technique. The criterion of the sampling is the use of mythological symbol. As a result, the research found there are several symbols, icons, and indexes used to represent neutral gender into Tiresias such as snakes, name of Tiresias, sex, body, and prophet. More than that, some figurative language also used to strengthen the implication of Tiresias implicitly in poem such as like a lady. Besides, typography also found to represent fluid identity such as ones and yous. Thus, this article is contributed to the embodiment of hybrid sign concept applied in literary analysis poetry. Moreover, it is also contributed to the development of gender theory which enlarge the knowledge about fluidity and neutral term of gender.